-7 +2 x(-3) +3 –(-10)-48÷6 bodmas rule
Answers
Answered by
1
Answer:
-7 + 2 × (-3) + 3 - (-10) - 48 ÷ 6
-7 - 6 + 3 + 10 - 8
- 7 - 6 + 13 - 8
- 7 - 7 - 8
- 7 - 15
= - 22
=> - 22
HOPE IT HELPS ❤️
THNKX MY ANSWERS ❤️
Answered by
4
Answer:
-76
Step-by-step explanation:
-7 +2(-3) +3 –(-10)-48÷6
=-7 +2(-3) +3 –(-10)-8
=-7-6+3+10-8
=-8
This is the correct answer
Hope its helpful
Similar questions
Math,
5 months ago
Social Sciences,
5 months ago
Biology,
5 months ago
English,
10 months ago
Accountancy,
10 months ago
Biology,
1 year ago